RIGHT TO EDUCATION OF MULTICULTURAL COUNTRIES FOR UNITY IN ASEAN COMMUNITY - Klomkul, Lampong; (Prasit Inkrungkao), Phra Rajvaramethi (ASEAN Journal of Religious and Cultural Research, 2019)
This article was written based on research paper related to educational management in ASEAN community, and focused on right to education of multicultural countries for unity in ASEAN community. This region is full of multicultural countries that have the different aspects of geography, religious, language, and nationalities of ethnicities. Right to education always contain in Education Act of ASEAN countries. Educational institutes apply the issue of right to education from education act by integrating into practices and design it in lesson plan and classroom activities. Education strategies have also being used for the guideline of educational development for all students in ASEAN community. Every student has the right in education and the opportunity of learning to reach their highest potential as the phrases called “No student left behind in Education within ASEAN Community”. In addition, 4-A scheme of right to education can apply for encouragement the quality of education development which is available, accessible, acceptable and adaptable.